Sikap dan Partisipasi Petani dalam Program Pelatihan Agribisnis Kedelai di Kabupaten Grobogan - Prasetyo, Agus Subhan; Gayatri, Siwi; Satmoko, Sriroso (Kadiri University, 2021)
Farmers' welfare is the central point of agricultural development. Nevertheless, farmers still have many problems. One of the solutions from the government is through farmer empowerment programs. It aims to increase the knowledge, attitudes, and skills of farmers to develop more productive farming. Proper farmers' attitudes and participation in supporting the program are required. Therefore, this research was conducted to analyze the attitude and participation of farmers in the soybean agribusiness training program in the Grobogan Regency. The research used a case study method. The technique of determining respondents used the census method. Respondents to the research were 109 farmers who participated in the soybean agribusiness training program. The data was collected by using a questionnaire, interview, observation, and literature study. Descriptive analysis and the Likert scale were used to analyze the data. Overall, the research results showed that the attitude of farmers to the soybean agribusiness training program is in a